Ensino de fração em contexto construcionista utilizando o software Wordwall - Souza, Giovanni Teixeira de (2024)
The limitations of schoolchildren in learning fractions, in understanding the part of the whole, and the meaning of the different ways in which they can be represented lead to questions. This problem occurs as a consequence of the need to abstract ideas, represent them in mathematical language and relate them to reality. The motivation is to develop learning by independently producing their own educational material and taking the lead in a more meaningful learning process. The research aims to analyze the learning of students in the early years of Elementary School in relation to the concepts and procedures of Fractions with an approach based on Constructionism from the creation of digital games. The research is characterized as qualitative, exploratory and interventional. Thirty-two students from the 5th Year - Morning, of mixed gender and age range between 10 and 11 years old, from a Municipal School located in Fortaleza - Ceará, participated in the study. Data collection was carried out in three phases with the application of: Initial Questionnaire, Didactic Sequence and Final Questionnaire. The Didactic Sequence presented 7 interventions based on the theoretical precepts of Constructionism and Techno-teaching, with students who constructed knowledge from the development of digital games using Wordwall software, thus characterizing it as the Educational Product. Data analysis occurred through direct interpretation of the information presented by the participating subjects, using Discursive Textual Analysis (DTA). Initially, the students presented conceptual and procedural ignorance about fractions, in addition to their composition; they were unable to define them or exemplify them. With the application of the Didactic Sequence, a significant advance was observed in this understanding linked to everyday experiences, given the deepening of their structural composition. The research and the Didactic Sequence will be made available to the entire academic and teaching community on a specific website; to the Fortaleza Department of Education, which supports the development of the research; in journals and academic dissemination events in the area of education and TDICs that emphasize teaching, learning and assessment. It is also intended to deepen and transform the proposal into advanced Doctoral research.